Amorphous/crystalline hybrid MoO2 nanosheets for high-energy lithium-ion capacitors. Issue 77 (15th September 2017) - Zhao, Xu; Wang, Hong-En; Cao, Jian; Cai, Wei; Sui, Jiehe
Abstract : A carbon-free MoO2 nanosheet with amorphous/crystalline hybrid domain exhibits high energy-high power lithium ion capacitors, which bridge the lithium ion batteries and supercapacitors. Abstract : A carbon-free MoO2 nanosheet with amorphous/crystalline hybrid domain was synthesized, and demonstrated to be an efficient host material for lithium-ion capacitors. Discrepant crystallinity in MoO2 shows unique boundaries, which can improve Li-ion diffusion through the electrode. Improved rate capacities and cycling stability open the door to design of high-performance lithium ion capacitor bridging batteries and supercapacitors.